Efforts to Improve National Insights for Junior High School Civics Teachers and Students in the Era of Disruption 4.0 - Jajang Hendar Hendrawan; Lili Halimah; Siti Amini (STAI Hubbulwathan Duri, 2023)
National insight in the era of disruption needs to be improved because the era of disruption, directly and indirectly, had an impact on human life, including increasing national insight. This study aims to determine the role of PPKn teachers in increasing students' national insight in the era of disruption 4.0. This research was conducted at a junior high school in Bandung Regency using a qualitative research approach. The research subjects were PPKn teachers, MTs Principals, Curriculum PKM, Student PKM, and students. Data collection in this study was carried out through observation, interviews, documentation studies, and the analysis technique used data reduction, data display, and conclusion drawing. The results of the study show that the role of Civics Teachers in increasing students' national insight in the Disruption Era 4.0 is 1) As a builder of devotion that is relevant to the school's vision and mission, namely the realization of a generation with SATF characters (Siddiq, Amanah, Tabligh and Fathanah), 2) As a character builder through extracurricular activities of Scouts, Paskibra and PMR, 3) Play a role in preparing the flag ceremony every Monday, commemorating the Commemoration of National Holidays (PHBN), 4) As a student mentor in the implementation of class picket habituation, clean Friday activities, social services, giving and giving charity, and 5) the teacher as a facilitator to invite, remind, and provide understanding to students in managing the environment with the spirit of honesty. This study concludes that Civics teachers play a role in increasing students' national insight in the era of disruption 4.0.